O conceito de responsabilidade como horizonte fundativo para a construção da base unitária ética-educação ambiental - Garção, Elvira Suzi dos Santos Bitencourt (2010)
The present work is about the interdisciplinary character of the environmental education, and its insert as pedagogic proposal aiming to establish the unitary basis ethicsenvironmental education, based on the principle of responsibility proposed by philosopher Hans Jonas, considering it as horizon foundation and parameter ethical regulative of the entropic actions which characterize the environmental crisis. Leaving of that theoretical apparatus, we attempted a new direction for the environmental education, tends as main objective to contribute with new philosophical elements, notably in the field of the ethics in the sense of enlarging the field of performance of the National Politics of Environmental Education, (NPEE, LAW no. 9.795, of April 27, 1999), Thus making possible, a new perspective for the environmental education, based on a dialogue with the Philosophy. While theoretical principle, the Ethics of the Responsibility, proposed by Jonas, aims to establish a new ethical paradigm, concerning in the respect of one to the other ones and everybody to the nature, allowing that wonders in that measured the men should be in the world and they should assure, in their projects, the existence of the future generations. We intended then to demonstrate that in the invigoration of a responsible pedagogic proposal, this should necessarily assume in its methodological and formative structure, an ethical perspective, gone back to the increment of the National Curriculum Parameters (NCP), in if being about traverse themes, to environment example, seeking its invigoration with basis in a philosophical perspective that bases actions and formative principles for the educational programs in the ambit of the public politics. Seeking, therefore, the effectuation of a new model for the environmental education concerning in Hans Jonas´s proposal ethics, we attempt a new element which stimulates the responsible actions, gone back to a dynamism contemplated in the collective praxis that translates its as social responsibility. This implies a new relationship on the nature. Therefore, in face of the related crisis, our research aims the search and the deepening of a new nature conception, starting from a new world understanding while habitation, home and habitat.